A study on the laws regulating migrant workers in Malaysia / Muhammad Kasyful Azim Shahlan, Rabiatul Adawiyah Sulaiman and 'Alia Nabeela Amran - Shahlan, Muhammad Kasyful Azim; Sulaiman, Rabiatul Adawiyah; Amran, 'Alia Nabeela (2012)
It is vital for any country that has migrant workers to also have laws governing them as well as protecting their rights. In Malaysia, the rights of the migrant workers are outlined in few local statutes such as the Employment Act 1955, the Workmen's Compensation Act 1952 and others. As for the United States, most of the laws pertaining to the rights of migrant workers are provided under Title 29 of the United States Code (U.S.C), which includes Fair Labor Standards Act 1938 and the Immigration Reform and Control Act 1986. The laws provided by both countries are quite the same but there are slight dissimilarities that can be addressed. The aim of this research is to identify the flaws of the local laws and make comparisons with what the United States has. This research also will provide recommendations as one of the ways to improvise the local laws.